Programma: 10-21 oktober: Johan v.d. Keuken Fototentoonstelling en retrospektief, slotavond One World Poetry '82 (1982)
Programma: 10-21 oktober: Johan v.d. Keuken Fototentoonstelling en retrospektief, slotavond One World Poetry '82.